Trees under Attack of a Thick Spider Web : New Ecological Phenomenon - Chander, Jagdish; Chauhan, Sanjeev K. (Indian Forester, 2017)
Following trapping of trees in a ghosty web in Haryana and Punjab during 2013-14, field study was carried out to investigate the new ecological phenomenon. The study revealed that due to population outbreak of dusky cotton bug/cotton seed bug (Oxycarenus hyalinipennis), nature applied its checks and balances and tent web spider (Cyrtophora citricola) came into action. It spun massive webs on different tree species to trap the ugly cotton seed bug as it preferred to rest in the cracks and crevices of stem surface of trees. The weaving of web on the trees coincided with the availability of cotton seed and cotton seed bug. As cotton crop was harvested, the seed bug also stopped breeding. The massive webs badly affected the leaves of trees, which in turn badly hampered the photosynthesis and the trees get exhausted. Trees lose their vigor and reproductive ability. The study emphasizes the need to bring the ecologists, foresters and agriculturists on a common platform for solution to this new ecological phenomenon leading to huge ecological and economic loss.